Comparative Analysis of Financial Performance of BUKU 4 Conventional Banks Before and During Covid-19 Pandemic - Mayuna Farah Wijayanti; Khoirul Hikmah (Universitas Mercu Buana, 2023)
Banks in Indonesia are facing a number of challenges amid the Covid-19 Pandemic. Banks will face several possible risks to financial performance. This study aims to determine the level of banking financial performance, especially in BUKU 4 Conventional Banks before and during the Covid-19 Pandemic for the 2019-2020 period using RGEC analysis (Risk Profile, Good Corporate Governance, Earnings, and Capital). The data used is secondary data obtained from the financial statements of banks included in the BUKU 4 category and processed using SPSS version 25. The results of the research on the financial performance of BUKU 4 Conventional Banks which can be seen from the Differential Test table (Paired Sample T-test and Wilcoxon test) show a decrease in several factors such as Risk profile and earnings factors. Meanwhile, the GCG and Capital factors show stable results both before and during the Covid-19 Pandemic